Prejudice in selected American and Iranian newspaper articles on Gaza crisis: A critical discourse study - Wahab Al-Addily, Rehab; Mahdi Al Shamiri, Sadiq (Edelweiss Applied Science and Technology, 2024)
Prejudice discourse is considered as one of the most important language uses usually invested in different social situations, particularly by in-group speech communities. This highlights the need to investigate this language phenomenon according to some interdisciplinary perspectives. So, this paper compares and contrasts from critical discourse perspective the prejudiced content used in the news coverage of American and Iranian newspapers' discourse as part of the discursive portrayal of the Israeli-Palestinian conflict during the 7th Oct. 2023 attack. Two articles were gathered from two opposing international newspapers, one is American (New York Post) and another is Iranian (Tehran Times). This paper aims at discovering prejudice's components and function, identifying the discursive strategies to determine the ideologies that allow a journalist to write a prejudice content. So, this helps the researcher to expos the differences and similarities in the selected data. To get a thorough critical comprehend of the nature of prejudice in the selected data, the researcher adopted a model for critical discourse analysis and applies qualitative and quantitative data analysis. The researcher finds that the cognitive, affected and behavioral components which are a reflection of an attitude in the function of publishing prejudiced content in the selected articles include semantic-strategies of lexicalization and aggregation and rhetorical-strategies of topo and contrast. The polarization of positive in-group self-representation and negative out-group representation in a racist and discriminatory way are the most prevalent ideologies that drive the creation of prejudiced content in the selected data. The articles differ in the sense that while the news coverage in Iranian was prejudiced "pro-Palestinians," American newspapers published prejudiced "pro-Israeli" articles. Although these two newspapers have adopted similar linguistic methods, they convey the news coverage of that event in some prejudiced way based on the newspaper's ideological perspective.